Students’ Motivation and English Learning Achievement in Senior High School Students - Dwinalida, Khairunnisa; Setiaji, Sholeh (Educalitra: English Education, Linguistics, and Literature Journal, 2022)
This study aims at investigating the relationship between students’ motivation and their English learning achievement of the tenth grade students of a Senior High School. 100 students were randomly chosen as the sample to evaluate and determine the students’ motivation and their English learning achievement. A set of questionnaire consisting of 18 items was used in this study to see the correlation between the two variables. Pearson correlation and descriptive analysis were used in analyzing data by using SPSS version 22.0. Pearson correlation shows an average level of correlation between motivation and English learning achievement. The finding shows that there was a significant relationship between students’ motivation and their English learning achievement. The findings could be useful for researchers and teachers in improving students’ achievement by conducting effective teaching and learning strategies to develop students’ motivation.